Diabetes Mellitus Secondary to Acute Pancreatitis in a Child with Wolf-Hirschhorn Syndrome - Asma Deeb (Case Reports in Endocrinology)
Wolf-Hirschhorn Syndrome (WHS) is a rare genetic disease caused by deletion in the short arm of chromosome 4. It is characterized by typical fascial features and a varying degree of intellectual disabilities and multiple systemic involvement. Epidemiological studies confirmed the association of acute pancreatitis with the development of diabetes. However, this association has not been reported in WHS. We report an 18-year-old girl with WHS who presented acutely with nonketotic Hyperglycemic Hyperosmolar Status (HHS) in association with severe acute pancreatitis. Her presentation was preceded by febrile illness with preauricular abscess. She was treated with fluids and insulin infusion and remained on insulin 18 months after presentation. Her parents are cousins and the mother was diagnosed with type 2 diabetes. She had negative autoantibodies and no signs of insulin resistance and her monogenic diabetes genetic testing was negative. Microarray study using WHS probe confirmed deletion of 4p chromosome. Acute pancreatitis is uncommon in children and development of diabetes following pancreatitis has not been reported in WHS. HHS is considerably less frequent than diabetes ketoacidosis in children. We highlight the complex presentation with HHS and acute pancreatitis leading to diabetes that required long term of insulin treatment.